Schistosomiasis mansoni as an occupational disease: the importance of establishing the link - Carneiro, Klitia de Jesus Saraiva Garrido; Carneiro, Klissia Saraiva Garrido; Carneiro, Cloves Silva (Saúde e Sociedade, 2023)
This study highlights the profile of rural workers with schistosomiasis mansoni, an endemic disease acquired during their work activities in flooded areas in the Baixada Maranhense. In order to analyze the social security and labor legislation used to grant benefits and the causal link that establishes the relationship between the work situation and the onset of the disease, we performed a bibliographical research on the topic and a documentary research on the formal legal plan of social security. This study addresses the need to recognize this relationship in endemic regions in order to improve what is proposed by the List of Work-Related Diseases.